Meningococcal carriage within households in the African meningitis belt: A longitudinal pilot study. Issue 2 (February 2018) - Basta, Nicole E.; Berthe, Abdoulaye; Keita, Mahamadou; Onwuchekwa, Uma; Tamboura, Boubou; Traore, Awa; Hassan-King, Musa; Manigart, Olivier; Nascimento, Maria; Stuart, James M.; Trotter, Caroline; Blake, Jayne; et al.
Highlights: We demonstrated the feasibility of conducting a longitudinal, household-based study of meningococcal carriage in the African meningitis belt. During the cross-sectional screening visit, the carriage prevalence was 5% (20 carriers among 400 participants from 116 households). Over 17 months, 1422 swabs were obtained from 202 people in 20 households. 73 carrier isolates identified; 33 people (16.3%) carried at least once. Among all swabs collected, 84% of isolates were non-groupable, though 6 W and 9 Y isolates were identified. No A, C, or X carriers were found. The meningococcal carriage duration, any serogroup, was 2.9 months (95% CI: 1.6, 5.4). The acquisition rate was 2.3% per month (95% CI: 1.3, 3.8). Summary: Objectives: Carriers of Neisseria meningitidis are a key source of transmission. In the African meningitis belt, where risk of meningococcal disease is highest, a greater understanding of meningococcal carriage dynamics is needed. Methods: We randomly selected an age-stratified sample of 400 residents from 116 households in Bamako, Mali, and collected pharyngeal swabs in May 2010. A month later, we enrolled all 202 residents of 20 of these households (6 with known carriers) and collected swabs monthly for 6 months prior to MenAfriVac vaccine introduction and returned 10 months later to collect swabs monthly for 3 months. We used standard bacteriological methods to identify N. meningitidis carriers and fit hidden Markov models to assess acquisition and clearance overall and by sex and age. Results: During the cross-sectional study 5.0% of individuals (20/400) were carriers. During the longitudinal study, 73 carriage events were identified from 1422 swabs analyzed, and 16.3% of individuals (33/202) were identified as carriers at least once. The majority of isolates were non-groupable; no serogroup A carriers were identified. Conclusions: Our results suggest that the duration of carriage with any N. meningitidis averages 2.9 months and that males and children acquire and lose carriage more frequently in an urban setting in Mali. Our study informed the design of a larger study implemented in seven countries of the African meningitis belt.